The The Distribution Chain of Sumbawa Forest Honey in Sumbawa Regency West Nusa Tenggara - Nila Wijayanti; Yadi Hartono; Alia Wartiningsih; Siti Nurwahidah (Musamus University, 2022)
This distribution chain of Sumbawa forest honey has several problems such as the long-distance of the forest from settlements, the fluctuated price of forest honey, which is depended on the quality and the distance to get the honey. The next problem is the high shipping cost to customers, and the packaging must be hygienic and safe. Sumbawa forest honey delivery to consumers must be in good. The purpose of this study is to analyze the marketing chain of Sumbawa forest honey in Sumbawa District, West Nusa Tenggara Indonesia. The method of determining location is done by purposive sampling, considering Sumbawa district is the center of Sumbawa forest honey. Respondent's sample determination was done by snowball sampling. The study was conducted by surveying the field by using a questionnaire with relevant institutions and carrying out documentation. The results showed that there were three types of distribution channels from Sumbawa forest honey. The first distribution channel is the honey hunter – the consumer. The second distribution channel is the honey hunter–honey enterprises-consumer. The third distribution chain is the honey hunter–honey enterprises–supermarket –the consumer. The price of honey received by consumers is not the same, depending on the length of the marketing chain. The marketing margin of the first distribution channel was Rp. 0,00. The second distribution were Rp. 60,000.00 and the third distribution were Rp. 50,000.00.Keywords: marketing, distribution chain, Sumbawa forest honey